2011
DOI: 10.1055/s-0031-1280268
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Effects of TongGuanWan, a Chinese Traditional Herbal Formula, in C57BL/KsJ-db/db Mice

Abstract: In the present study, the anti-diabetic effects of a traditional Chinese medicinal formula extract, TongGuanWan, were investigated in type 2 diabetic animals. It was orally administered to C57BL/KsJ-db/db mice once a day for 4 weeks at the doses of 62, 125, and 250 mg/kg body weight. TongGuanWan significantly lowered the blood glucose and glycosylated haemoglobin levels as well as improved the glucose tolerance in db/db mice. The serum triglyceride levels in the db/db mice were significantly decreased, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
2
17
1
Order By: Relevance
“…Metabolic assessment revealed that MGF treatment limited body weight gain. While we cannot point toward a single phenolic compound, responsible for observed beneficial effects, previous studies have shown that mangiferin may control glucose levels in high fat diet treated mice (1), and mangiferin extracts or derivatives also reduce glycemia in db/db mice (21,53). In our hands, glucose levels were not significantly affected by MGF treatment.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Metabolic assessment revealed that MGF treatment limited body weight gain. While we cannot point toward a single phenolic compound, responsible for observed beneficial effects, previous studies have shown that mangiferin may control glucose levels in high fat diet treated mice (1), and mangiferin extracts or derivatives also reduce glycemia in db/db mice (21,53). In our hands, glucose levels were not significantly affected by MGF treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…Natural polyphenols, and concretely Mangifera Indica Linn extract has been shown to have antioxidant, antidiabetic and anti-inflammatory activities [for review see (33,54)]. While we cannot point toward a single phenolic compound, responsible for observed beneficial effects, previous studies have shown that mangiferin may control glucose levels in high fat diet treated mice (1), and mangiferin extracts or derivatives also reduce glycemia in db/db mice (21,53). Also, no evidence of adverse side effects, at estimated dietary intake levels, have been reported for phenolic compounds in our extract [(44), for review (22,54)], and we did not detect any obvious differences in treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that berberine exerts its anti-diabetic effect in ZDF rats by moderating the diabetic metabolism. These results are similar to those obtained in previous studies [7,16,17,18,19]. The administered dosage (300mg/kg) of berberine was determined according to the equation used for the adult maximal dosage in the clinic [7].…”
Section: Discussionsupporting
confidence: 84%
“…Rhizoma Anemarrhenae (Zhimu in Chinese), a wellknown traditional Chinese medicinal herb, which is officially listed in the Chinese Pharmacopoeia, has been effectively used for febrile diseases in oriental clinical practices. Timosaponin A-III (TAIII), a steroidal saponin isolated from the rhizomes of Anemarrhena asphodeloides (AA), has been credited with a wide spectrum of bioactivities, including improving learning and memory (16), inhibiting inflammation (17), suppressing allergic reaction (18), controlling hyperglycemic (19,20), activating autophagy (21) and inducing cancer cells apoptosis (22)(23)(24). However, the ability of TAIII to reverse MDR has not been reported.…”
Section: Introductionmentioning
confidence: 99%